Effect of ambient temperature on outpatient admission for osteoarthritis and rheumatoid arthritis in a subtropical Chinese city - Desheng Zhao; Jian Cheng; Ping Bao; Yanwu Zhang; Fengjuan Liang; Hao Wang; Xu Wang; Shiyuan Fang; Hong Su (BMC, 2022)
Abstract Background Current findings on the impact of weather conditions on osteoarthritis (OA) and rheumatoid arthritis (RA) are sparse and not conclusive. This study aimed to investigate the relationship between temperature change and OA/RA admission. Methods Daily OA/RA admission, meteorological data and pollutants from 1 January 2014 to 31 December 2017 in Hefei, China, were collected. We quantified the relationship between ambient temperature and OA/RA admission using a distributed lag nonlinear model (DLNM). Stratified analyses by gender and age were also examined. Results Temperature decrease was significantly associated with RA admission (25th percentile of temperature versus 50th percentile of temperature), with the acute and largest effect at current days lag (RR: 1.057, 95%CI: 1.005-1.111). However, no significant association between temperature and OA admission was observed. When conducting subgroup analyses by individual characteristics, we found that females and patients aged 41-65 years were more vulnerable to temperature decrease than males, patients aged 0-40 and ≧66 years, respectively. Conclusions This study suggested that temperature decrease was a risk factor for increases in RA admission. Females and patients aged 41-65 years were particularly vulnerable to the effect of temperature decrease.